ChemInform Abstract: Complexation Phenomena and Dynamics at Work in the Lithiation Reactions of Small‐Ring Heterocycles: Regio‐ and Stereoselectivity. Issue 48 (2nd December 2014) - Capriati, Vito; Florio, Saverio; Luisi, Renzo
Abstract Review: [75 refs.